(untitled) (Biological Sciences - PJSIR, 2002)
The molecular band appearing at 6V = 770 cm-1 on the blue wing of the intercombination Cd (326.1 nm) line broadened by Cd pressure has been in vestigated. This band was interpreted as a rain bow sateJl ite accompanying the dipole 2 forbidden Cd (314.1 nm) line associated with the 53P 51 S transition. The profile of this band has been calculated 0 using the semiclassical model developed by Szudy and Baylis. To obtain this profile the interatomic potential of the molecular state lu and the dipole moment associated with this band have been modified to give the best fit profile with the experimental one.